Decreasing central line-associated bloodstream infections rates in intensive care units in low- and middle- income countries: An INICC approach - Rosenthal, Victor D.; Jin, Zhilin; Brown, Eric C.; Dongol,, Reshma; De Moros, Daisy A.; Alarcon-Rua, Johana; Perez, Valentina; Stagnaro, Juan P.; Alkhawaja, Safaa Abdulaziz; Jimenez-Alvarez, Luisa F.; Cano-Medina, Yuliana A.; Valderrama-Beltran, Sandra L.; et al. (Elsevier BV, 2023)
Background: Central line (CL)-associated bloodstream infections (CLABSIs) occurring in the ICU are common and associated with a high burden.